f(0) = 1
g(0) = 1
f(x+1) = ((f(x))^2 + (g(x))^2)
g(x+1) = f(x)g(x)
Is it possible to find a closed form for these two functions?
MathOverflow is a question and answer site for professional mathematicians. It only takes a minute to sign up.
Sign up to join this communityf(0) = 1
g(0) = 1
f(x+1) = ((f(x))^2 + (g(x))^2)
g(x+1) = f(x)g(x)
Is it possible to find a closed form for these two functions?
$f(n)$ is sequence A073833 and $g(n)$ is sequence A073834 in the OEIS, you can find all information there.